The relationship between stunting and breastfeeding cessation in toddlers - Simanjuntak, Agnes Septrya; Pratama, Irza Haicha; Simanullang, Partogi Hasiholan (Institute of Computer Science (IOCS), 2025)
This study aimed to analyze the relationship between breastfeeding cessation and the incidence of stunting in toddlers in Medan City. A total of 124 toddlers participated, with 50% experiencing stunting. Descriptive analysis showed that most mothers stopped breastfeeding between 0–6 months (50.81%), while the majority of toddlers (89.52%) consumed formula milk until 54–60 months. The Kolmogorov-Smirnov normality test indicated non-normal data distribution (p = 0.000), leading to the use of Spearman’s rank correlation. Results revealed a significant moderate positive correlation between breastfeeding cessation age and stunting incidence (r = 0.432; p = 0.000), indicating that earlier cessation of breastfeeding increases the risk of stunting. These findings align with previous research emphasizing the critical role of breastfeeding in stunting prevention. Although formula milk consumption was common, it did not significantly influence stunting alone. Therefore, stunting prevention efforts should prioritize exclusive breastfeeding for six months and continued breastfeeding up to two years, alongside improved complementary feeding, environmental sanitation, and maternal nutrition. A multisectoral approach is essential to effectively reduce stunting prevalence and improve toddler health in Medan City.